'Learning to re-create your life': an evaluation of a residential mental health recovery program. (3rd May 2020) - Dorozenko, Kate P.; Martin, Robyn; Gillieatt, Sue; Milbourn, Ben
ABSTRACT: Personal recovery is enshrined in Australian and international mental health policy. Services seeking to support people to lead meaningful lives of their choosing require mental health professionals to embrace alternative practices. In this paper, we present the findings of an evaluation of a 15-week residential program aspiring to promote personal recovery in Perth, Western Australia. Group work is the main service delivery mode, and the program is premised on the belief that a therapeutic peer community environment has the potential to create conditions for recovery. Semi-structured interviews were conducted with 13 consumers following graduation, and at six months follow-up ( n = 9) which explored their experiences of the program, its strengths, areas for improvement, and impact. Data were analysed using a general inductive approach which was guided by the evaluation objectives. Participants reported that the Recovery House was emotionally challenging, personally transformative, and unlike any other service or program experience. Key elements that supported recovery were the live-in nature of the program; the emphasis on commitment and taking personal responsibility; use of a peer community as a therapeutic tool; and the focus on deep emotional healing and making meaning. Challenges included communal living, and transitioning back into the community post-program. Recovery House represents an attempt to depart from traditional relationships and ways of working within mental health services by emphasising self-determination, equal relationships, and creating opportunities to deeply explore emotional distress. Evaluation findings suggest that intensive therapeutic group work may be a powerful contributor to supporting recovery.